Fixed-time adaptive sliding mode-based trajectory tracking control for Wheeled Mobile Robot: Theoretical development and real-time implementation - Brahim Moudoud; Hicham Aissaoui (e-Prime: Advances in Electrical Engineering, Electronics and Energy)
Wheeled mobile robots (WMR) are common autonomous systems requiring efficient control methods. This work investigates fixed-time adaptive sliding mode control (FxT-ASMC) for the trajectory tracking task of a WMR subject to disturbances/uncertainties. The developed control strategy seeks to avoid the chattering problem, cope with disturbances when the upper limit is undefined, and enhance the convergence of the system states. Indeed, a new adaptive technique has been developed to effectively handle disturbances, even in the absence of prior knowledge regarding their upper bound. This technique consists in estimating the switching gain for each channel separately. On the other hand, an appropriate design of the reaching law ensures the fixed-time convergence of the sliding variables to zero. Additionally, sliding variables are designed in a way that guarantees the tracking errors will stabilize within a set amount of time. This kind of convergence was demonstrated using Lyapunov stability theory. In order to realize the trajectory tracking control structure, the FxT-ASMC system is incorporated with a classical kinematic controller. The efficiency of the suggested control methodology is proven via simulations and practical implementation.